2018
DOI: 10.1213/ane.0000000000003722
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Complement Protein Gene Expression Before and After Surgery in Opioid-Consuming and Opioid-Naive Patients

Abstract: Opioids may influence inflammation. We compared genes associated with pain and inflammation in patients who consumed opioids (3-120 mg of oral morphine equivalents per day) with those who did not for differential expression. White blood cells were assayed in 20 patients presenting for total lower extremity joint replacement. We focused on messenger ribonucleic acid expression of complement proteins. We report that the expression of a complement inhibitor, complement 4 binding protein A, was reduced, and the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…With emerging evidence showing increased levels of cytokines and glial cell activation in the postoperative brain, neuroinflammation has been implicated as a critical contributory factor to the development of PNDs [ 137 , 138 ]. Previous clinical studies have observed that various peripheral surgical trauma induces complement activation, including C3a, C5a, C5–C9, factor B, and other regulatory complement components in the blood [ 139 , 140 , 141 , 142 ]. Interestingly, C3 in astrocytes and C3aR in microglia are both increased in the brain after tibial fracture surgery, which further accelerates synapse loss, cognitive impairment, and blood–CSF barrier dysfunction [ 45 ].…”
Section: The Complement System In Neurodegenerative Diseasesmentioning
confidence: 99%
“…With emerging evidence showing increased levels of cytokines and glial cell activation in the postoperative brain, neuroinflammation has been implicated as a critical contributory factor to the development of PNDs [ 137 , 138 ]. Previous clinical studies have observed that various peripheral surgical trauma induces complement activation, including C3a, C5a, C5–C9, factor B, and other regulatory complement components in the blood [ 139 , 140 , 141 , 142 ]. Interestingly, C3 in astrocytes and C3aR in microglia are both increased in the brain after tibial fracture surgery, which further accelerates synapse loss, cognitive impairment, and blood–CSF barrier dysfunction [ 45 ].…”
Section: The Complement System In Neurodegenerative Diseasesmentioning
confidence: 99%